Qualidade de vida relacionada à saúde e sarcopenia em idosos da comunidade: fatores associados e comparação com o contexto pandêmico da covid-19 - Camargo, Guilherme Gasparini (2022)
Sarcopenic older adults are at greater risk of falls, hospitalization, death, diminished functional and cognitive capacity and a poorer quality of life compared to non-sarcopenic older adults. The aims of the present study were to analyze factors associated with health-related quality of life (HRQoL – total and domains) in community-dwelling sarcopenic older adults and determine possible differences in the perception of HRQoL among these individuals before and during the COVID-19 pandemic. Two studies were developed. The first involved data from a previous study with 54 and 117 older adults with and without sarcopenia, respectively, according to the European Working Group on Sarcopenia in Older People 2. The Short Form Health Survey (SF-36) was used to assess quality of life. Comparative and linear regression analyses were performed. Differences between groups were found regarding health conditions and the perception of HRQoL, with worse outcomes among sarcopenic older adults. Perceived HRQoL was poorer in the sarcopenic group compared to the non-sarcopenic group in the following SF-36 dimensions: physical functioning (<0.001), physical role functioning (<0.029), general health state (p<0.001), vitality (<0.011) and social role functioning (p<0.001). All models related to HRQoL in sarcopenic older adults were statistically significant, with the best prediction related to physical functioning (83.3%). The factors associated with low HRQoL were being married (p<0.001), being widowed (p<0.022), depressive symptoms (p<0.007), anxiety/depression (p<0.005) and pain (p<0.009) in the general health state domain; nutritional status (p<0.045) in the social role domain; and depressive symptoms (p<0.005) in the mental health domain. The second study compared the HRQoL of sarcopenic older adults before and during the COVID-19 pandemic using the Sarcopenic Quality of Life (SarQoL®) scale. For the pre-pandemic period, a databank was used with information collected at the homes of the older adults. During the pandemic, the same individuals were interviewed by telephone. Interviews lasted an average of 15 minutes. Half of the older adults felt vulnerable to contamination by SARS-CoV-2 (p<0.001), felt some or considerable fear (p<0.013), a minority felt isolated and a reduction occurred in activities of daily living (p<0.001). No differences were found in the comparison of the pre-pandemic and pandemic period regarding the perception of overall HRQoL or any of the dimensions, with the exceptions of locomotion (p = 0.013) and body composition (p = 0.005). In conclusion, older adults with sarcopenia had poorer HRQoL in all domains of the SF-36 compared to the non-sarcopenic group, except for the bodily pain, emotional role functioning and mental health domains. Being married, being widowed and having depressive symptoms, anxiety and pain were associated with poorer HRQoL in the general health state domain, nutritional status was associated with the outcome in the social role domain and depressive symptoms were associated in the mental health domain. Unlike what was expected, no differences were found for the majority of HRQoL domains evaluated using the SarQoL® scale before and during the pandemic among sarcopenic older adults. These findings are important to the planning of care for older adults in the primary care context.